2007
DOI: 10.1111/j.1442-9071.2007.01529.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of statin drugs and aspirin on progression in open‐angle glaucoma suspects using confocal scanning laser ophthalmoscopy

Abstract: Statin drugs may be associated with slowed progression of optic nerve parameters in glaucoma suspects as measured by CSLO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
8

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 39 publications
2
44
0
8
Order By: Relevance
“…First, the authors stated that the studies by De Castro et al 4 and Leung et al 6 consisted of representative or somewhat representative samples of statin users in the selection domain. However, the representativeness of both studies is uncertain because they were conducted in university-based eye centers where the population coverage was not described.…”
Section: The Process Of Appraising the Quality Of Evidence Of The Incmentioning
confidence: 99%
See 3 more Smart Citations
“…First, the authors stated that the studies by De Castro et al 4 and Leung et al 6 consisted of representative or somewhat representative samples of statin users in the selection domain. However, the representativeness of both studies is uncertain because they were conducted in university-based eye centers where the population coverage was not described.…”
Section: The Process Of Appraising the Quality Of Evidence Of The Incmentioning
confidence: 99%
“…The authors categorized the patients in the study by Stein et al 5 who had conversion from suspected glaucoma to definite glaucoma, as well as the patients in the study by De Castro et al 4 who had within-normal-limits result on the glaucoma hemifield test at the start of study (i.e., open-angle glaucoma [OAG] suspect as defined in the study) but outside normal limits at the last visit (i.e., OAG case as defined in the study) as having glaucoma progression. They also categorized the patients with normal-tension glaucoma in the study by Leung et al 6 who had visual field defect at the start of the study and visual field progression at the end of the study as having glaucoma progression.…”
Section: Placement Of Studies In the Meta-analysismentioning
confidence: 99%
See 2 more Smart Citations
“…4 Also, in a study by De Castro et al, it was reported that the use of statins for at least 23 months showed optic nerve head changes suggestive of a protective effect against glaucoma progression and RNFL thickness. 5 Therefore, it would be better to consider the medication status while performing RVC, OPA, RNFL and macular thickness measurements.…”
Section: Sirmentioning
confidence: 99%